1998
DOI: 10.1161/01.str.29.11.2245
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Ischemic Events With High Positive Anticardiolipin Antibodies

Abstract: Background and Purpose-The aim of our study was to characterize the patient profile and prognostic value associated with high positive IgG (Ͼ100 GPL) anticardiolipin antibodies (aCL). Methods-We studied the clinical, laboratory, radiological, and prospective historical features of ischemic cerebrovascular disease in patients with Ͼ100 GPL titers. From our neurology department, 27 consecutive patients were prospectively identified and followed up (mean follow-up time, 34 months). Results-The mean age of our coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 47 publications
4
43
0
3
Order By: Relevance
“…Another study 12 showed that individuals with IgG-aCL of Ͼ40 GPL units had more prior strokes and more frequent subsequent thrombo-occlusive events and death, whereas still another study 13 reported that the presence of aCL did not confer an increased risk for subsequent thromboocclusive events and death. In a recent study, 14,15 cerebro-vascular events were associated with high levels of IgGaCL (Ͼ100 GPL) in relatively young adults.…”
mentioning
confidence: 93%
“…Another study 12 showed that individuals with IgG-aCL of Ͼ40 GPL units had more prior strokes and more frequent subsequent thrombo-occlusive events and death, whereas still another study 13 reported that the presence of aCL did not confer an increased risk for subsequent thromboocclusive events and death. In a recent study, 14,15 cerebro-vascular events were associated with high levels of IgGaCL (Ͼ100 GPL) in relatively young adults.…”
mentioning
confidence: 93%
“…These and other studies, however, appear to reach a consensus that although generally GPL and LAC show a good correlation among themselves and with the thrombotic manifestations of APS, mainly thrombosis, LAC correlates much more with venous thrombosis [27,28]. Some studies have shown a correlation of the IgA isotype of aCL with thrombocytopenia [29] while the IgM isotype of aCL has been shown to correlate with auto-immune haemolytic anaemia [30].…”
Section: Discussionmentioning
confidence: 95%
“…Данные проявления не считают клиническими критериями, но их наличие в совокупности с аФЛ представляет собой важный диагностический фак-тор для детей с АФС [4,9,46].…”
Section: антифосфолипидный синдром у детейunclassified
“…Головные боли, включая мигрень, и ишемические инсуль-ты являются главными неврологическими про-явлениями АФС [15,19]. Были изучены и дока-заны влияния таких факторов, как пол, наличие или отсутствие мигрени в семейном анамнезе, использование пероральных контрацептивов, вы-сокое артериальное давление, сахарный диабет, заболевания сердца и курение, на возникновение неврологической симптоматики при АФС [36,46]. Наличие аФЛ -доказанный фактор риска развития инсультов, при этом исследование плаз-менного звена гемостаза необходимо проводить всем молодым людям с мигренью и пациентам до 50 лет с инсультом в анамнезе.…”
Section: поражение центральной нервной системыunclassified